Pelatihan Penggunaan Aplikasi Geogebra for Personal Computer bagi Guru MGMP Matematika SMA Kabupaten Barito Kuala - Soraya Djamilah; Mega Puspitorini (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This activity aims to increase the understanding and knowledge of mathematics teachers at using the geogebra application for personal computers to support mathematics learning, as a learning media in mathematics. The method that is used in this activity is short training of using the geogebra application for personal computers. Participants were given training by presentations and demonstrations at using the Geogebra application. The participants of this activity are teachers who are members of the Mathematics Subject Teachers' Consultation (MGMP) for High School Mathematics in Barito Kuala Regency can take part in the training well and enthusiastically